Amylin Receptor: A Potential Therapeutic Target for Alzheimer's Disease. Issue 8 (August 2017) - Fu, Wen; Patel, Aarti; Kimura, Ryoichi; Soudy, Rania; Jhamandas, Jack H.
Abstract : Alzheimer'sdisease (AD) is a progressive neurodegenerative disorder, characterized by senile plaques constituting extracellular deposits of β-amyloid (Aβ) fibrils. Since Aβ accumulation in the brain is considered an early event preceding, by decades, cognitive dysfunction, disease-modifying treatments are aimed at facilitating clearance of this protein from the brain or ameliorating its toxic effects. Recent studies have identified the amylin receptor as a capable mediator of the deleterious actions of Aβ and furthermore, administration of amylin receptor-based peptides has been shown to improve spatial memory and learning in transgenic mouse models of AD. Here, by discussing available evidence, we posit that the amylin receptor could be considered a potential therapeutic target for AD, and present the rationale for using amylin receptor antagonists to treat this debilitating condition. Trends: Accumulation of amyloid beta protein in the brain is considered an early and seminal event in AD pathogenesis. Current treatment strategies for AD have focused on the inhibition of this protein and/or increasing its clearance from the brain. The amylin receptor has been identified as a target for the expression of deleterious effects of Aβ. Amylin receptor-based compounds have been shown to improve memory and learning in in vitro and in vivo transgenic mouse models of AD. The presence of amylin receptors on three critical cell types implicated in AD pathogenesis – neurons, microglia, and endothelial cells of the brain vasculature – is shedding new light on the contributions of this receptor to AD. Drugs that improve cognitive and pathological deficits in preclinical models of AD could serve as a novel platform in developing future disease-modifying therapies for AD and potentially for other neurodegenerative diseases.